Surface confined heteroleptic copper(II)-polypyridyl complexes for photonuclease activity - Singh, Vikram; Mondal, Prakash C.; Kumar, Anup; Jeyachandran, Yekkoni Lakshmanan; Awasthi, Satish K.; Gupta, Rinkoo D.; Zharnikov, Michael (Chemical communications, 2014)
Heteroleptic copper(II)-polypyridyl complexes with extended π-conjugated, aromatic terminal units were immobilized on glass/Si substrates to intercalate DNA and cleave it upon photoexposure. Photonuclease activity is shown to be high, well reproducible and non-destructible towards the assembled complexes.
Gesehen am 24.09.2020